Pengaruh Pemanfaatan Teknologi Informasi dan Handling Complaint Terhadap Minat Nasabah Menggunakan Internet Banking di Bank BRI Syariah Kantor Cabang Pembantu Majalaya - Irma Monika Desi Deria; Ryzki Wiryawan (Journal of Applied Islamic Economics and Finance, 2022)
This research is motivated by fluctuations in customer interest. Based on the results of the study, it shows that the cause of the fluctuation in customer interest is influenced by the use of Information Technology and Handling Complaints at Bank BRI Syariah Majalaya Sub-Branch Office. This study aims to determine how the influence of the use of information technology and complaint handling on customer interest in using internet banking at Bank BRI Syariah KCP Majalaya. Either partially or simultaneously. The object of this research is the use of information technology, complaint handling and customer interest at Bank BRI Syariah Majalaya Sub-Branch Office. As for the type of research using associative quantitative research and the type of data using primary data. Collecting data through observation, interviews, literature study and questionnaires. The sample in this study used probability sampling with a simple random sampling technique. The results of the study show that there is an effect of the use of information technology on customer interest with the results of the t test where the value of tcount > ttable (8,820 > 1.29471). There is an effect of handling complaints on customer interest with the results of the t-test where the value of tcount > ttable (7.147 > 1.29471). Simultaneously there is an effect of the use of information technology and complaint handling on customer interest with the results of the F test that Fcount > Ftable (39.249 > 4.95)